Circadian rhythms in haematological malignancies: therapeutic potential and personalised interventions - Marjan Motiei; Raed Abu-Dawud; Angela Relógio; Chalid Assaf (EBioMedicine)
Summary: The circadian clock, a fundamental cellular mechanism, regulates the rhythmic expression of numerous genes and biological processes across various organs. Disruptions in this system, driven by genetic or environmental factors, have been reported to be involved in cancer progression. This review explores the role of the circadian clock in cancer hallmarks and its impact on cellular homeostasis within haematological malignancies. Drawing on findings from in vitro, in vivo, and clinical trials, this review highlights the potential of clock genes as diagnostic and prognostic biomarkers, and as therapeutic targets for optimising treatment timing. It discusses how circadian rhythms can enhance treatment efficacy through both pharmacological and non-pharmacological interventions, outlining strategies for optimising dosing schedules and implementing personalised chronobiological interventions, with a particular focus on haematological malignancies, including cutaneous lymphoma. Ongoing research holds promise for advancing personalised therapeutic approaches and ultimately improving cancer care standards.